MAGNDATA: towards a database of magnetic structures. II. The incommensurate case. Issue 6 (24th October 2016) - Gallego, Samuel V.; Perez-Mato, J. Manuel; Elcoro, Luis; Tasci, Emre S.; Hanson, Robert M.; Aroyo, Mois I.; Madariaga, Gotzon
Abstract : A basic free database with more than 400 magnetic structures has been developed. Its section on incommensurate structures, described under the framework of superspace symmetry, is presented. Abstract : A free web page under the name MAGNDATA, which provides detailed quantitative information on more than 400 published magnetic structures, has been made available at the Bilbao Crystallographic Server (http://www.cryst.ehu.es ). It includes both commensurate and incommensurate structures. In the first article in this series, the information available on commensurate magnetic structures was presented [Gallego, Perez‐Mato, Elcoro, Tasci, Hanson, Momma, Aroyo & Madariaga (2016). J. Appl. Cryst. 49, 1750–1776]. In this second article, the subset of the database devoted to incommensurate magnetic structures is discussed. These structures are described using magnetic superspace groups, i.e. a direct extension of the non‐magnetic superspace groups, which is the standard approach in the description of aperiodic crystals. The use of magnetic superspace symmetry ensures a robust and unambiguous description of both atomic positions and magnetic moments within a common unique formalism. The point‐group symmetry of each structure is derived from its magnetic superspace group, and any macroscopic tensor property of interest governed by this point‐group symmetry can be retrieved through direct links to other programs of the Bilbao Crystallographic Server. The fact that incommensurate magnetic structures are often reported with ambiguous or incomplete information has made it impossible to include in this collection a good number of the published structures which were initially considered. However, as a proof of concept, the published data of about 30 structures have been re‐interpreted and transformed, and together with ten structures where the superspace formalism was directly employed, they form this section of MAGNDATA . The relevant symmetry of most of the structures could be identified with an epikernel or isotropy subgroup of one irreducible representation of the space group of the parent phase, but in some cases several irreducible representations are active. Any entry of the collection can be visualized using the online tools available on the Bilbao server or can be retrieved as a magCIF file, a file format under development by the International Union of Crystallography. These CIF‐like files are supported by visualization programs like Jmol and by analysis programs like JANA and ISODISTORT .